Japan as an immigration nation demographic change, economic necessity, and the human community concept - Sakanaka, Hidenori (Lexington Books, 2020)
In this treatise by veteran Japanese immigration specialist, Hidenori Sakanaka-the former director of the Tokyo Regional Immigration Bureau-proposes sweeping changes to Japan's immigration policy to address the interrelated problems of a rapidly declining population and a decrease in working-age adults.